A Komparasi Penggunaan AC-OF-SM-1B (Kabel Dc 1 Seling) Dengan AC-OF-SM-1-3SL (Kabel Dc 3 Seling) Dalam Keamanaan Jaringan Kabel Fiber Optik - Omar, Dhafid; Juvent Alessandro Patuden; Yustian Servanda; Agus Wijayanto (Journal Of Informatics And Busisnes, 2025)
Fiber optic cable network security is a crucial aspect in ensuring the quality of service and sustainability of telecommunications infrastructure. One important element in the installation of such a network is the selection of the type of Drop Core (DC) cable used, especially in distribution areas that are prone to physical and environmental disturbances. This study discusses the comparison between two types of DC cables commonly used, namely AC-OF-SM-1B (DC cable with 1 strand) and AC-OF-SM-1-3SL (DC cable with 3 strand), in the context of effectiveness on fiber optic network security. This study was conducted using direct field observation methods, supported by discussions with technicians in the field, and evaluation of historical data on disturbances and damage from the use of both types of cables. The findings show that AC-OF-SM-1-3SL has a stronger structure, is able to withstand tensile loads and external pressure better, and is more resistant to environmental disturbances such as strong wind gusts and intervention from human activities. Meanwhile, AC-OF-SM-1B cables are lighter and more economical but have a higher level of vulnerability to external disturbances. These findings are expected to be a technical reference in making decisions regarding the selection of cable types in fiber optic network projects, especially in areas with a high risk of physical disruption.